2013
DOI: 10.4269/ajtmh.12-0458
|View full text |Cite
|
Sign up to set email alerts
|

Vector Blood Meals Are an Early Indicator of the Effectiveness of the Ecohealth Approach in Halting Chagas Transmission in Guatemala

Abstract: Abstract. A novel method using vector blood meal sources to assess the impact of control efforts on the risk of transmission of Chagas disease was tested in the village of El Tule, Jutiapa, Guatemala. Control used Ecohealth interventions, where villagers ameliorated the factors identified as most important for transmission. First, after an initial insecticide application, house walls were plastered. Later, bedroom floors were improved and domestic animals were moved outdoors. Only vector blood meal sources rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…Blood meal analyses showed that chickens, rodents and dogs are important blood sources in this region, as in another study in a nearby Municipality [51]. Chickens are an important part of household nutrition and economy, and are allowed to nest inside the house.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Blood meal analyses showed that chickens, rodents and dogs are important blood sources in this region, as in another study in a nearby Municipality [51]. Chickens are an important part of household nutrition and economy, and are allowed to nest inside the house.…”
Section: Discussionmentioning
confidence: 53%
“…The molecular detection of a blood meal indicates blood meals taken within the last 2–3 weeks [53]. The detection of multiple blood meals in nymphs, including human blood meals in outdoor structures, suggests that immature stages actively move in search of blood meals, as found in another Municipality [51] and for T. infestans in Peru and Argentina [4], [6]. This may be a situation that facilitates house re-infestation, as nymphs may find peridomestic shelters in rodent nesting areas, found within and outside the household, that do not receive insecticide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of houses with good quality complete plastering increased by 21% and 13% in the two Ecohealth-intervention villages; one control village showed a 4% decline and another showed an 9% increase in good quality complete plastering. 24 After 5 years of interventions, the percentage of Triatoma dimidiata feeding on humans dropped from 38% to 7% and Trypanosoma cruzi infection in Triatoma dimidiata dropped from 49% to 16% in one intervention village, 26 whereas in the other intervention village, the number of Triatoma dimidiata dropped drastically and it was not possible to obtain an estimate of percent of insects feeding on humans. Infestation levels in that village have remained under the 5% threshold set by the Guatemalan Ministry of Health for insecticide application 27 and also under the suggested threshold of infestation (8%) at which Trypanosoma cruzi transmission becomes unlikely.…”
Section: Introductionmentioning
confidence: 99%
“…Fragments of the cytochrome oxidase b locus were previously used for taxonomic and phylogenetic studies [14] while the 12S and 16S rRNA loci were used to identify vertebrate species in forensic studies [15]. Some of these mitochondrial loci have also been used to identify blood meals in vectors [16], [17], and as potential indicators of community based interventions against Chagas disease [18]. These assays relied on DNA sequence analysis for species determination.…”
Section: Introductionmentioning
confidence: 99%